The serotonin 1A (5-HT1A) receptor as a pharmacological target in depression - Smith, ALW; Harmer, CJ; Cowen, PJ; Murphy, SE (Springer Nature, 2023)
Clinical depression is a common, debilitating and heterogenous disorder. Existing treatments for depression are inadequate for a significant minority of patients and new approaches are urgently needed. A wealth of evidence implicates the serotonin 1A (5-HT1A) receptor in the pathophysiology of depression. Stimulation of the 5-HT1A receptor is an existing therapeutic target for treating depression and anxiety, using drugs such as buspirone and tandospirone. However, activation of 5-HT1A raphe autoreceptors has also been suggested to be responsible for the delay in the therapeutic action of conventional antidepressants such as selective serotonin reuptake inhibitors (SSRIs). This narrative review provides a brief overview of the 5-HT1A receptor, the evidence implicating it in depression and in the effects of conventional antidepressant treatment. We highlight that pre- and post-synaptic 5-HT1A receptors may have divergent roles in the pathophysiology and treatment of depression. To date, developing this understanding to progress therapeutic discovery has been limited, partly due to a paucity of specific pharmacological probes suitable for use in humans. The development of 5-HT1A ‘biased agonism’, using compounds such as NLX-101, offers the opportunity to further elucidate the roles of pre- and post-synaptic 5-HT1A receptors. We describe how experimental medicine approaches can be helpful in profiling the effects of 5-HT1A receptor modulation on the different clinical domains of depression, and outline some potential neurocognitive models that could be used to test the effects of 5-HT1A biased agonists.